The jazz of cladistics*. Issue 5 (3rd September 2017) - Assis, Leandro C.S.
Abstract : In this metaphorical 'composition', I comment on nine 'dissonant chords' related to the drowning out of cladistic performance: (1) DNA-based phylogenetic hypotheses supported only by bootstrap values and without molecular synapomorphies; (2) the use of molecular data to the exclusion of morphological data, with the classification of clades diagnosed by morphological plesiomorphies plus bootstrap values; (3) neglect of the results of the congruence test and how they are interpreted; (4) the combination of character optimization using both model-based and parsimony methods, and its consequences; (5) the need to effectively integrate ontogeny and phylogeny; (6) the estimation of the ages of clades based on molecular-clock analyses; (7) the belief that new methods, theories, and hypotheses are more reliable than old ones, with the idea that model-based analyses achieve better results than parsimony analyses; (8) the false assumption of the irrelevance of classification; and (9) clashes amongst cladists themselves, who endorse distinct methods, philosophies, and theories. Finally, I present 10 'refrains' in order to intensify the cladistic performance.